Performance Feedback in Organizations: Understanding the Functions, Forms, and Important Features. Issue 1 (2nd January 2023) - Johnson, Douglas A.; Johnson, C. Merle; Dave, Priyanka
ABSTRACT: Feedback surrounds our personal and professional worlds, informing us about what worked and what did not. Within workplace settings, it is important to understand how feedback operates in order to deliberately and carefully craft performance information that, when delivered, generates desirable organizational outcomes. The current paper examines the many potential functions of feedback, including details on how such functions might be established. Behavioral investigations into how to best structure and deliver feedback are detailed, along with considerations of factors that may impact the reception of feedback. Finally, using the current literature as a blueprint, several possible research directions are suggested that would fit well within a behavior analytic perspective.